2014
DOI: 10.1002/dev.21258
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal deprivation and the duration of reunion time on rat pup ultrasonic vocalization responses to isolation: Possible implications for human infant studies

Abstract: In a paradigm that may serve as a translational model for maternal separation experiences of human infants in neonatal intensive care units, we examined how the duration of reunion with the dam influenced the phenomenon of maternal potentiation of ultrasonic vocalizations, in which isolated rat pups increase rates of vocalization following brief interactions with dams. We report that maternal potentiation in 12-13 day-old rats did not occur after reunions with their anesthetized dam that lasted longer than 15-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Rodent pup USVs are believed to denote negative affective states such as distress, as they decrease with the administration of anxiolytic drugs like benzodiazepines (Miczek et al, 1995; Zimmerberg et al, 1994). Consistent with this, isolation from the mother leads to potentiation of USV calls from the pups, indicating a state of anxiety or distress (Hofer et al, 2002; Shair et al, 2015).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Rodent pup USVs are believed to denote negative affective states such as distress, as they decrease with the administration of anxiolytic drugs like benzodiazepines (Miczek et al, 1995; Zimmerberg et al, 1994). Consistent with this, isolation from the mother leads to potentiation of USV calls from the pups, indicating a state of anxiety or distress (Hofer et al, 2002; Shair et al, 2015).…”
Section: Discussionsupporting
confidence: 57%
“…We also detected fewer calls from paternal PCB F3 pups than VEH after a period of separation, indicating either a baseline difference in the number of calls, or that these PCB pups experienced less distress when separated from their mother. Although the decline in calling could be a consequence of the decreased time that F2 PCB mothers spent on the nest and nursing on P3, other studies have shown that a decrease in maternal care behaviors resulted in greater anxiety-like behaviors in the offspring (Bowers et al, 2013; Shair et al, 2015). The F3 paternal lineage PCB pups, although devoid of direct exposure to EDCs, could inherit altered epigenetic marks via the mature sperm in the paternal germline as well (Probst et al, 2009), causing alterations in vocalization behavior of the offspring and subsequently altering the dam’s maternal care behaviors.…”
Section: Discussionmentioning
confidence: 95%
“…It is well established that repeated, early-life maternal separation (MS) has adverse consequences on both physiology and behaviour 25 . The present study is the first to extend the MS paradigm to acoustic characteristics of ultrasonic vocalizations (USVs) beyond a one-time MS behavioural test 26,27 . Our findings show that MS has repercussions on multiple acoustic features of USVs during a stressful test on postnatal day (PND) 12, when we acquired isolation-induced USVs.…”
Section: Discussionmentioning
confidence: 99%
“…Finding maternal but not paternal USV potentiation after a brief reunion is consistent with the hypothesis that potentiation reflects a form of dysregulation resulting from the unexpected interruption of “coregulation” of physiological and behavioral systems inherent, and specific to, mother–infant interactions. When the mother–pup reunion is allowed to continue for at least 15 min, pups do not express USV potentiation (Shair et al, ), presumably because separations after prolonged periods of coregulation are less disruptive to the infant.…”
Section: Discussionmentioning
confidence: 99%